INVESTIGATION OF THE EFFECT OF POSITIVE PERCEPTION AND MENTAL TOUGHNESS LEVELS ON MOTIVATION OF SUCCESS IN ELITE MOUNTAIN RUNNING ATHLETES - Karharman, Abdulselam; Bayansalduz, Mehmet (Acta Scientiae et Intellectus, 2024)
The aim of this study is to investigate the effect of 18 year old and over elite mountain running athletes’ positive perception and mental toughness levels on success motivation participated in Turkey mountain running championship. The research group consists of a total of 166 athletes. In the study; Mental Touhness Scale (ZRS) adapted to Turkish by Erdogan (2016) and developed by Madrigal, Hamill and Gill (2013) and Positive Perception Scale (PSS) developed by Icekson and Pines (2013), adapted to Turkish by Akın and Kaya (2015) and Sports Specific Success Motivation Scale developed by Willis (1982) and adapted to Turkish by Tiryaki and Godelek (1997) were used. Data were edited in Microssoft Excel 2003 program and analyzed using Spss 20.0 for windows package program. Descriptive analysis methods were used to determine the distribution of personal information of the athletes involved; cross-table analysis and percentage table analysis were used. For the scales applied in the study; In order to test whether the subscales of the two scales show normal distribution, a normality test of 0.05 significance level was applied. In order to make comparisons between the sub-dimensions of both scales according to whether the data were distributed normally or not, for parametric (anova / independent sample t-test) or for nonparametric (Kruskal Wallis / Mann Whitney-U) statistic was used. Multiple regression analysis with 0.01 significance level was performed to determine the effect levels of independent variables on positive perception and sport-specific success motivation.